2017
DOI: 10.3126/jnhrc.v15i2.18182
|View full text |Cite
|
Sign up to set email alerts
|

Iodine and Thyroid Function Status, and Anti-thyroid Peroxidase Antibody among Pregnant Women in Eastern Nepal

Abstract: INTRODUCTION

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 18 publications
2
18
2
Order By: Relevance
“…A 41% prevalence of subclinical or overt hypothyroidism in pregnant women has been reported in a hospital based study in Western Nepal [33]. Another study on iodine deficiency and hypothyroidism amongst pregnant women found 3.2% of the cases positive for antibodies to thyroid peroxidase and 18.5% of the women to have inadequate levels (<150 µg/L) of iodine [34]. In a study of children diagnosed with congenital hypothyroidism [9], thyroid agenesis, dyshormogenesis and ectopic thyroid were the most common causes of low thyroid hormones.…”
Section: 1tshmentioning
confidence: 89%
“…A 41% prevalence of subclinical or overt hypothyroidism in pregnant women has been reported in a hospital based study in Western Nepal [33]. Another study on iodine deficiency and hypothyroidism amongst pregnant women found 3.2% of the cases positive for antibodies to thyroid peroxidase and 18.5% of the women to have inadequate levels (<150 µg/L) of iodine [34]. In a study of children diagnosed with congenital hypothyroidism [9], thyroid agenesis, dyshormogenesis and ectopic thyroid were the most common causes of low thyroid hormones.…”
Section: 1tshmentioning
confidence: 89%
“…LSCS is significantly higher in hypothyroids than euthyroids (48.5% versus 18.8%, p value equal to 19 In comparison to other studies done in different part of world prevalence of hypothyroidism is very high in Nepal. Nutritional factor may be one of the causes for this as there is high prevalance of iodine deficiency hypothyroidism in Nepal.…”
Section: Resultsmentioning
confidence: 52%
“…Studies from Nepal shows very high prevalence of hypothyroidism. 18,19 By treating hypothyroidism in early pregnancy, we can reduce the fetal and maternal mortality and come up with excellent fetal maternal outcome.…”
Section: Resultsmentioning
confidence: 99%
“…The median thyroglobulin level in the children with insufficient UIC was 17.5 ng/mL. Our previous study among pregnant women of eastern Nepal reported median Tg of 6.5 ng/mL [17]. Thyroglobulin increment in plasma is also seen with thyroid mass, inflammation and hyperactivity of TSH [18].…”
Section: Main Textmentioning
confidence: 81%
“…In addition, there are other causative factors for thyroid disorders such as thyroid autoimmunity which might have been missed from this subgroup [17]. Thyroid function is said to be impaired in both the condition of iodine deficiency and excess [1].…”
Section: Main Textmentioning
confidence: 99%